Recontextualisation and reappropriation of social and political discourses in toilet graffiti at the University of the Western Cape - Ferris, Fiona; Banda, Felix (Stellenbosch Papers in Linguistics Plus, 2018)
Applying notions of interdiscursivity, commodification of discourse (Fairclough 1993) and semiotic remediation (Bolter and Grusin 2000), this paper analyses toilet graffiti in men’s and women’s toilets at the University of the Western Cape in order to capture how the toilet walls become platforms where texts associated with other genres and discourses are appropriated, remediated, and transformed for expanded production and consumption of meaning. In turn, it explores the ideological and identity manifestations of the inscriptions in the transformed and remediated semiotic material, and the dialogicality and the trajectory of the texts across space and time. Thereafter, a discussion is presented of the implications of the expanded meaning potentials resulting from blended and recontextualized discourses from other genres and cultural contexts.